Relationship of speed-strength and anthropometric indicators of highly qualified football players 16-17 years of different roles - Kalinin, E. M.; Savin, D. N.; Kuzmichev, V. A.; Leksakov, A. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the relationship between the anthropometric and speed-strength characteristics of football players in laboratory and field conditions to identify differences in these indicators relative to their role.